2007
DOI: 10.1017/s1461145707007705
|View full text |Cite
|
Sign up to set email alerts
|

Effects of naltrexone on cocaine- and sucrose-seeking behaviour in response to associated stimuli in rats

Abstract: The non-selective opioid receptor antagonist naltrexone reduces cocaine-induced reinstatement of drugseeking behaviour in abstinent rats. The current study sought to determine whether the opioid system is also involved in cocaine-seeking behaviour induced by cocaine-associated stimuli in abstinent rats. Adult male rats were trained to press a lever either to self-administer cocaine or to obtain sucrose pellets in the presence of distinctive discriminative and conditioned stimuli. After a period of extinction, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
31
1

Year Published

2007
2007
2016
2016

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 39 publications
(35 citation statements)
references
References 25 publications
2
31
1
Order By: Relevance
“…The processing of these different types of cues appears to require different neural substrates (Phillips and LeDoux 1992;Holland and Bouton 1999). Second, we observed the most reliable effects of naloxone at day 30 of forced abstinence while Burattini et al (2007) tested responding after about 15 days of extinction. There is also the consideration of differences in efficacy to explain the discrepancy between naloxone and naltrexone; however, this is unlikely as the naltrexone dose (2.5 mg/kg) was similar to our higher doses.…”
Section: Discussionmentioning
confidence: 66%
See 3 more Smart Citations
“…The processing of these different types of cues appears to require different neural substrates (Phillips and LeDoux 1992;Holland and Bouton 1999). Second, we observed the most reliable effects of naloxone at day 30 of forced abstinence while Burattini et al (2007) tested responding after about 15 days of extinction. There is also the consideration of differences in efficacy to explain the discrepancy between naloxone and naltrexone; however, this is unlikely as the naltrexone dose (2.5 mg/kg) was similar to our higher doses.…”
Section: Discussionmentioning
confidence: 66%
“…In effect, the animal model is validated. However, a recent study of the effect of a single dose of naltrexone on responding in the presence of a discriminative stimulus, previously indicating the availability of sucrose, did not find any effect of naltrexone on conditioned responding (Burattini et al 2007). This inconsistency is likely due to several methodological issues.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…In agreement, pharmacological studies have shown that MOR antagonists reduced cocaine relapse in rats (Tang et al, 2005). Furthermore, the non-selective opioid antagonist naltrexone reduced cue-induced cocaine-seeking behavior (Burattini et al, 2008), and had no effects on cocaine priming-induced reinstatement in rats (Comer et al, 1993), although repeated naltrexone treatment suppressed this priming-induced reinstatement . Accordingly, microinjection of selective MOR agonists into the nucleus accumbens reinstated cocaine-seeking behavior in rats (Simmons and Self, 2009).…”
Section: Discussionmentioning
confidence: 70%